Urban flood modeling in Karlovassi area - Samos Island. - Boglis, A.; Evelpidou, N.; Vassilopoulos, A.; Lekkas, D.; Foudoulis, I.; Gournelos, Th. (11th International Conference on Environmental Science and Technology (CEST 2009), 2009)
As flash flood events are becoming more frequent, the development of flood estimation methods for areas with limited or lack of data has attracted the interest of many scientists. The aim of the present paper is to develop a GIS based methodology in order to study the flood risk in Karlovassi basin. The annual probability of a flood event is relatively high at Karlovassi area (Samos Island – Greece). Especially, after the forest fires that took place in the summer of 2000, during which 90.000 hectares were burnt in Kerketeas Mountain, the phenomenon has become more intense. Primary data were collected from maps, literature, aerial photos and field work. The collected information data were analyzed through the use of the software ArcGIS in order to generate the appropriate background for the formation of the flood risk model. All the input parameters were weighted and the model was calibrated in situ through field work. The proposed methodology and the preliminary results, as exported for the Karlovassi area, prove the suitability of GIS-based methods in the creation of flood risk maps.